Smart plant care system using IoT and cloud computing / Muhammad Syamim Samsudin - Samsudin, Muhammad Syamim (2020)
From the agricultural sector, humans can provide absolutely indispensable food and energy sources. It has become one of the most important industries in human history. New technologies using the Internet of Things (IoT) can further develop the agricultural industry. The research aims to provide a smart agricultural system based on IoT. The goal of this project is to develop an IoT system to monitor the condition of plant health remotely using cloud to monitor the humidity, temperature and soil moisture levels received of the crops. The methodology used in this project is the Spiral model. The Spiral model consists of five phases; requirement, design, coding and testing. The target of this project is to focus on staff, students and lecturer have authorize to at UiTM Perlis. In of the system development, in the end of development, to measure and evaluate the user's understanding of this smart plant care system, the usability and user acceptance test has been conducted. most users agree that this system can be used to monitor the condition of crops accurately from the results of tests performed on them. Future work, the system can be improved on the automatic fertilization of crops process and continues power source.